Streptomyces chumphonensis sp. nov., isolated from marine sediments - Wongsakorn Phongsopitanun; Chitti Thawai; Khanit Suwanborirux; Takuji Kudo; Moriya Ohkuma; Somboon Tanasupawat (My University, 2014)
Two actinomycete strains, KK1-2(T) and CPB4-7, were isolated from marine sediments collected in Chumphon province, Thailand. Chumphon province, Thailand. Their taxonomic positions were determined using a polyphasic approach. The morphological, cultural and chemotaxonomic characteristics of these isolates were consistent with the classification of the strains as representing a member of the genus Streptomyces. They contained LL-diaminopimelic acid in their cell wall peptidoglycan; the whole-cell sugars were ribose and glucose. The predominant menaquinones were MK9-(H6) and MK9-(H8). The major polar lipids were phosphatidylethanolamine, phosphatidylinositol, diphosphatidylglycerol, phosphatidylglycerol and phosphatidylinositol mannosides. The predominant cellular fatty acids were anteiso-C(15 : 0), iso-C(16 : 0) and iso-C(15 : 0). On the basis of 16S rRNA gene sequence similarity studies, these isolates were determined to be closely related to Streptomyces xinghaiensis JCM 16958(T) (98.2%), Streptomyces rimosus subsp. paromomycinus JCM 4541(T) (98.1%), Streptomyces sclerotialus JCM 4828(T) (98.1%) and Streptomyces flocculus JCM 4476(T) (98.0%). The G+C contents of the genomic DNA of strains KK1-2(T) and CPB4-7 were 73.3 and 74.2 mol%, respectively. They could be clearly distinguished from the related type strains by a low DNA-DNA relatedness and phenotypic differences. On the basis of these results, these strains represent a novel species of the genus Streptomyces, for which the name Streptomyces chumphonensis sp. nov. (type strain KK1-2(T) = JCM 18522(T) = TISTR 2106(T) = PCU 330(T)) is proposed.
Keywords: Genomics and Phylogenetic Studies